2010
DOI: 10.1080/17439884.2010.494432
|View full text |Cite
|
Sign up to set email alerts
|

Serious playground: usingSecond Lifeto engage high school students in urban planning

Abstract: Virtual world platforms such as Second Life have been successfully used in educational contexts to motivate and engage learners. This article reports on an exploratory workshop involving a group of high school students using Second Life for an urban planning project. Young people are traditionally an under-represented demographic when it comes to participating in urban planning and decision making processes. The research team developed activities that combined technology with a constructivist approach to learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The growing presence of digital devices at home raises many questions about their influence on adolescents' reading and writing competence [23]. The use of technology is undoubtedly a source of motivation for the majority of adolescents, and some studies have demonstrated a positive relation between technology use and academic results [24,25]. Nevertheless, the use of technology mainly arouses controversy, with its supporters and detractors in terms of the effect on students' academic performance [26,27].…”
Section: Ict Outside School and Their Influence On Students' Academicmentioning
confidence: 99%
“…The growing presence of digital devices at home raises many questions about their influence on adolescents' reading and writing competence [23]. The use of technology is undoubtedly a source of motivation for the majority of adolescents, and some studies have demonstrated a positive relation between technology use and academic results [24,25]. Nevertheless, the use of technology mainly arouses controversy, with its supporters and detractors in terms of the effect on students' academic performance [26,27].…”
Section: Ict Outside School and Their Influence On Students' Academicmentioning
confidence: 99%
“…Interactive 3D virtual environment has made a significant impact on educational thinking (Mallan et al 2010;Goldparvar-Fard et al 2010). Web-based virtual 3D game environment was Computing in Civil Engineering (2012) Downloaded from ascelibrary.org by New York University on 08/02/15.…”
Section: Introductionmentioning
confidence: 99%
“…2 nd Life as a major player in 3D virtual game environment gained significant interests from educational community due to its potential of creating an immersive virtual learning environment (Mallan et al 2010;Warburton 2009). However, one of its major drawbacks is the difficulty to create realistic built environments using its own primitive-shape library, and it has significant issues in its interoperability with BIM models (Ku 2011).…”
Section: Related Workmentioning
confidence: 99%